2017
DOI: 10.1299/jamdsm.2017jamdsm0084
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the load distribution of splined joints under gear loading conditions

Abstract: Splined joints are commonly used to transmit rotary motion from a shaft to machine elements such as gears. While computationally efficient spline load distribution models have recently been proposed, there is no validated load distribution model of a splined joint due to lack of high-fidelity experimental data. Accordingly, this study aims to establish an extensive experimental database on load distributions of splined joints subject to both spur and helical gear loading conditions. A quasi-static, spline-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In Figure 7 the von Mises stress is scaled by the nominal von Mises stress. 9 In the modelling the spline tooth extends across the whole shaft length to avoid the influence from run-out.…”
Section: Modelling Torsion By Finite Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 7 the von Mises stress is scaled by the nominal von Mises stress. 9 In the modelling the spline tooth extends across the whole shaft length to avoid the influence from run-out.…”
Section: Modelling Torsion By Finite Elementsmentioning
confidence: 99%
“…In Figure 7 the von Mises stress is scaled by the nominal von Mises stress. 9 In the modelling the spline tooth extends across the whole shaft length to avoid the influence from run-out. In Figure 7 we see that for this case we have a stress concentration factor K vM = 3:34, the high stress occurs in the hub at outer surface where we have a singularity in the contact between shaft and hub, corresponding to point c in Figure 5.…”
Section: Modelling Torsion By Finite Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…By inputting any load component and any initial separation, the load distribution characteristics of spline under various combined loads can be determined. Benatar et al [10] established an extensive experimental database, developed a special quasi-static spline testing device, tested the load distribution of spline connection under spur gear and helical gear load, and compared it with the spline load distribution mode. Liu et al utilized finite element method to the whole Ravigneaux planetary gear set with two ring gears with external spline teeth, it was found that the middle zone between two external spline teeth has large stress due to impact [11].…”
Section: Introductionmentioning
confidence: 99%